Could effective microorganisms improve tolerance of UCB1 pistachio to salinity? - Fazeli Salmani, Abdollatif; Davarynejad, Gholam Hossein; Abedi, Bahram (Comunicata Scientiae, 2020)
Salinity is one of the most important limiting factors for plant growth which can reduce its undesirable effects through stress modulators. In order to investigate the effect of effective microorganisms (EM) on morphological indices and activity of some enzymes in UCB1 rootstock pistachio under salinity stress, a factorial experiment was conducted as a randomized complete blocks design. Factors included were salinity stress at four levels (0.7, 5, 10 and 13.6 dS m-1) and EM at two levels (0, 1%) with three replications. Treatments were applied for three months on plants. The results showed that increasing salinity decreased seedling height, leaf number, stem and root fresh and dry weight, but the activity of (CAT), peroxidase (POD) and ascorbate peroxidase (AXP) enzymes increased compared to control treatment, whereas EM application showed that concentration of 1% of this fertilizer increased the measured morphological indices and decreased the activity of CAT, POD and AXP enzymes. Interaction effect between salinity and EM was significant only on morphological indices. According to the results, it can be stated that application of EM could reduce adverse effects of salinity stress on the UCB1 rootstock.